Routledge international handbook of diversity studies
1 online resource (xviii, 404 pages)
Keywords: "In recent years the concept of 'diversity' has gained a leading place in academic thought, business practice and public policy worldwide. Although variously used, 'diversity' tends to refer to patterns of social difference in terms of certain key categories. Today the foremost categories shaping discourses and policies of diversity include race, ethnicity, religion, gender, disability, sexuality and age; further important notions include class, language, locality, lifestyle and legal status. The Routledge Handbook of Diversity Studies will examine a range of such concepts along with historical and contemporary cases concerning social and political dynamics surrounding them. With contributions by experts spanning Sociology, Anthropology, Political Science, History and Geography, the Handbook will be a key resource for students, social scientists and professionals. It will represent a landmark volume within a field that has become, and will continue to be, one of the most significant global topics of concern throughout the twenty-first century"--